Taste and food reinforcement in non-overweight youth. (1st August 2015) - Epstein, Leonard H.; Carr, Katelyn A.; Scheid, Jennifer L.; Gebre, Eden; O'Brien, Alexis; Paluch, Rocco A.; Temple, Jennifer L.
Highlights: Food reinforcement is related to energy intake, weight gain and obesity. There is no research on major taste groups and food reinforcement. Sweet foods were the most reinforcing. Food reinforcement was related to energy intake. Food reinforcement was a stronger predictor of energy intake than liking. Abstract: Food reinforcement is related to increased energy intake, cross-sectionally related to obesity and prospectively related to weight gain in children, adolescents and adults. There is very limited research on how different characteristics of food are related to food reinforcement, and none on how foods from different taste categories (sweet, savory, salty) are related to food reinforcement. We tested differences in food reinforcement for favorite foods in these categories and used a reinforcing value questionnaire to assess how food reinforcement was related to energy intake in 198 non-overweight 8- to 12-year-old children. Results showed stronger food reinforcement for sweet foods in comparison to savory or salty foods. In multiple regression models, controlling for child sex, minority status and age, average reinforcing value was related to total energy and fat intake, and reinforcing value of savory foods was related to total energy and fat intake. Factor analysis showed one factor, the motivation to eat, rather than separate factors based on different taste categories. Liking ratings were unrelated to total energy intake. These results suggest that while there are differences in the reinforcing value of food by taste groups, there are no strong differences in the relationship between reinforcing value of food by taste groups and energy or macronutrient intake.